2021
DOI: 10.31328/jsed.v4i2.2272
|View full text |Cite
|
Sign up to set email alerts
|

Institution reinforcement of mosque in social economic empowerment of small traders community

Abstract: Historically, mosque is the center for human civilization with various activities covering social, economy, and culture. However, its function have been shifted and specialized into a place of worship.  This paper aims to describe the contribution of the great mosque of Attaqwa Pancor in social economic empowerment, particularly small businesses in Pancor, East Lombok, Nusa Tenggara Barat (NTB). The Data are collected through observation, interview, and document study. The result of the analysis shows that mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Scholars have long discussed the role of religious institutions in the social and spiritual life of society (Azhar, 2019;Idris & Putra, 2021;McLeigh & Taylor, 2020;Sheikhi et al, 2021). In Islamic civilization, mosques represent a crucial aspect of the culture (Efiyanti et al, 2021), as the term 'mosque' literally translates to submission to the creator. The Quran has made mention of mosques 28 times.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have long discussed the role of religious institutions in the social and spiritual life of society (Azhar, 2019;Idris & Putra, 2021;McLeigh & Taylor, 2020;Sheikhi et al, 2021). In Islamic civilization, mosques represent a crucial aspect of the culture (Efiyanti et al, 2021), as the term 'mosque' literally translates to submission to the creator. The Quran has made mention of mosques 28 times.…”
Section: Discussionmentioning
confidence: 99%
“…Psychologically empowered employees are more dedicated to their jobs and companies [42,43]. Other researchers have found that empowered workers are more interested in their organizations and have lower quitting rates [44][45][46]. Salminen and Miettinen [46] demonstrate that supervisory support for growth improves affective commitment (AC), raising their chance of remaining in their present position.…”
Section: Psychological Empowerment and Affective Commitmentmentioning
confidence: 99%
“…Apart from helping members and the public obtain cheap financing, MbSC can potentially increase the growth of MSMEs (Efiyanti et al, 2021) and effectively eliminate the presence of moneylenders in the community (Nur & Zubair, 2020;Triana & Naqiyah, 2020). Nevertheless, MbSC needs more energetic human resources (Rusydiana & Devi, 2018) to perform even better, which is currently lacking where nearly 85% of MbSC staff are from the 50s and 60s generations (Adriani et al, 2019).…”
Section: 1mentioning
confidence: 99%